Multi-user channel estimation for uplink OFDMA systems based on the random-set theory - Yuan JING; Bin NIU; Ying-ying TAI (Tongxin xuebao)
For the uplink OFDMA systems,a random-set theory based multi-user channel estimation algorithm was proposed.In the proposed algorithm,states of the users the multi-path channels were modeled and described by a finite random set.Then the Bayes filtering was utilized to formulate the problem of multi-user channel estimation.To obtain both the accepted channel estimation performance and low computational complexity,the Rao-Blackwellized particle filtering algorithm was applied to approximately solve this Bayes filtering problem with small number of particles.Simulation results show the effectiveness of the proposed algorithm.